Examining Internal Control Unit in Improving Personnel Performance on Islamic Higher Education - As'ad As'ad (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2021)
The internal control unit (ICU) can not only reduce fraud in financial matters, misappropriation of assets, but also can improve the performance of personnel in state Islamic universities. The purpose of this research is to study the role of the internal control unit in improving the performance of human resources. This study uses a qualitative approach with the type of case study at the State Islamic University of Sulthan Thaha Saifuddin Jambi. The research subjects are the head of the internal control unit, the secretary, lecturers and employees. Data were collected through in-depth interviews, document review, and observation, then the data were analyzed descriptively. Research findings that the internal control unit plays an important role in higher education governance which includes supervision of finance, assets, and human resources. The existence of an internal control unit has been able to improve and improve the performance of individuals and the performance of units, institutions, which have an impact on the performance of the institution.